The Effect of Traditional Clog Games in Improving Balance, Agility, and Coordination of Early Childhood Children at the Educare Center Kindergarten in Medan - Safran Safran; Fatma Gustina (Continuous Education: Journal of Science and Research, 2026)
This study aimed to determine the effect of the traditional bakiak game on improving the gross motor skills of children aged 5–6 years at Erwita Educare Centre Kindergarten in Medan. Gross motor development is an essential aspect of early childhood education because it supports children’s physical growth, coordination, balance, and participation in learning activities. This study employed a quantitative pre-experimental method using a one-group pretest–posttest design. The participants were 10 children aged 5–6 years, consisting of six girls and four boys. Gross motor skills were assessed before and after the treatment through observations of four indicators: speed, agility, flexibility, and balance. The treatment was conducted by engaging children in the traditional bakiak game, which requires coordinated body movements, cooperation, and balance control. The findings showed a significant improvement in children’s gross motor skills after the intervention. The average pretest score increased from 45.0 to 85.0 in the posttest. Improvements were found in all measured aspects, with average increases of 35 points in speed, 38 points in agility, 35 points in flexibility, and 35 points in balance. The Wilcoxon Signed Rank Test yielded a significance value of 0.001, which was lower than 0.05, indicating a significant difference between pretest and posttest scores. Therefore, the traditional bakiak game was effective in improving the gross motor skills of early childhood children.